Cromatin and core particles formed from the inner histones and synthetic polydeoxyribonucleotides of defined sequence. - Simpson, R T (1979)
Chicken erythrocyte inner histones (H2A, H2B, H3 and H4) were associated with the two complementary homopolymeric polydeoxyribonucleotides and the two alternating copolymeric polydeoxyribonucleotides. No evidence for formation of chromatin-like structures was obtained for the complexes with poly(dG) . poly(dC) or poly(dA) . poly(dT). Both poly (dGdC) . poly(dGdC) and poly(dAdT) . poly(dAdT) could be folded by histones to yield material digested by DNAase I to multiples of about 10 and by staphylococcal nuclease to 146 bp core particles. Due to the lack of sequence heterogeniety in the complex of histones with poly(dAdT) . poly(dAdT), core particles with remarkable fine structural detail are obtained. The internal organization of DNA in the AT-containing and GC-containing core particles appears not to be identical.